Developments with experimental and investigational drugs for axial spondyloarthritis. (3rd July 2017) - Clavel, Gaëlle; Boissier, Marie-Christophe; Sigaux, Johanna; Semerano, Luca
ABSTRACT: Introduction : Axial spondyloarthritis (AxS pA) is a chronic inflammatory disease for which, until recently, there were no valid therapeutic alternatives to TNF-α blocking agents. This unmet clinical need led to explore several therapeutic targets, from proinflammatory cytokines to intracellular signaling systems. The recent approval of Secukinumab, an anti-IL-17A monoclonal antibody, marked a new step in the evolution of AxSpA treatment. Areas covered : the authors review and discuss all the biological or synthetic agents that are currently developed or that have been tested in AxSpA. News from relevant press releases by manufacturers on past, current and future developments are also reported. Several agents that target IL-17 are currently between phase 2 and 3 of clinical development. Ustekinumab, a monoclonal antibody that blocks IL-23 and IL-12 is also in phase 3 after encouraging results from a pilot study. Expert opinion : The advent of agents that target the IL-23/IL-17 axis promises to reshape the therapeutic landscape for AxSpA in the next few years. Open questions in the research agenda for these agents involve their positioning in the therapeutic strategy, their efficacy on the spectrum of skeletal and extraskeletal manifestations of AxSpA, their effect on new bone formation and their long-term tolerance.